IMPLEMENTASI KONSELING MODEL RATIONAL EMOTIF UNTUK MENANGGULANGI GANGGUAN EMOSIONAL SISWA KELAS IX A SMP PGRI 3 DENPASAR TAHUN PELAJARAN 2018/2019 - Giri, Putu Agus Semara Putra (Widyadari : Jurnal Pendidikan, 2019)
In the world of education in the current era of globalization, there are many cases found in schools that are related to the problem of emotional disorders in students who are influenced by internal and external factors. So that it will have an adverse effect on the purpose of education itself. Where education is a conscious and planned effort to realize the learning process so that students actively develop their potential to have a spiritual spiritual level, self-control, personality, intelligence, noble character and skills needed by themselves, society, nation and country.          The purpose of this study was to determine whether the emotive rational model counseling could overcome emotional disturbances in class IXA students of SMP PGRI 3 Denpasar academic year 2018/2019. The object of this study was students of class IXA SMP PGRI 3 Denpasar, with a total number of 48 people. Students who have problems are as many as 5 people consisting of 3 men and 2 women, problems faced around emotional disorders such as low self-esteem, unhappiness, anxiety, mental disorders, lack of self-control, sadness without reason and guilt.          Students who take counseling services on emotive rational models of effort to overcome students' emotional disturbances are given for two cycles allocated for one month. After being given counseling services to the rational emotive model to overcome the emotional disturbances of students, students showed a decrease in emotional disturbances, compared to emotional disorders before the action of counseling guidance services. Based on the analysis, and discussion, it can be concluded that the emotive rational counseling service can overcome the emotional disturbances of class IXA students of SMP PGRI 3 Denpasar, 2018/2019 academic year.